Hoping for the best, prepared for the worst: can we perform remote data collection in sport sciences? - Souza, H. L.; Bernardes, B. P.; Dos Prazeres, E. O.; Arriel, R. A.; Meireles, A.; Camilo, G. B.; Mota, G. R.; Marocolo, M. (Journal of Applied Physiology, 2022)
The current COVID-19 pandemic has challenged all professionalfield areas and established social distancing behaviors and stay-at-home measures as the"new normal."Mandatoryquarantine at some points in time also changed health careservices, which required alternative approaches for healthcare procedures, such as telemedicine appointments (1), aim-ing to reduce the risk of virus transmission. Just as theCOVID-19 pandemic changed the way health care was provided, it may be time to rethink new possibilities for data acquisition and research designs in sport sciences.